The Predictive Power of Academic Motivation of Primary School Teacher Candidates on Their Self-Efficacy in the First Reading and Writing Teaching - Dilşat Uzunoğlu; Sabri Sıdeklı (Mehmet KURUDAYIOĞLU, 2023)
The aim of this study was to determine the predictive power of academic motivation of primary school teacher candidates on their self-efficacy in the first reading and writing teaching. To this end, the study was designed as correlational survey model. The universe of the study consisted of public university students at Grades 2, 3 and 4 of the department of primary school education in 2021-2022 spring semester and the participants were selected randomly for this study. As data collection tool, "Academic Motivation Scale" was used in order to determine the motivational level of candidate primary school teachers, whereas "Self-Efficacy Scale for the First Reading and Writing Teaching" was used to evaluate the self-efficacy of the primary school teacher candidates in the first reading and writing teaching. Designed on "Google Forms", these two scales were administered to teacher candidates in one online session. For the data collection procedure, two weeks were allowed for data collection. At the end of this duration, the data was analyzed. As for data analysis, descriptive statistical analysis and simple linear regression analysis were used in the study. As a result of the study, it was seen that both academic motivation level and self-efficacy level of the teacher candidates on the first reading and writing teaching were at high level. Additionally, it was realized that there was a significant relationship between academic motivation and self-efficacy in the first reading and writing teaching, and also it was stated that academic motivation significantly predicted the level of self-efficacy in the first reading and writing teaching. Besides, academic motivation accounted for 22% of the changes in the self-efficacy scores in the first reading and writing teaching.